The CpxA/CpxR Two-Component System Affects Biofilm Formation and Virulence in Actinobacillus pleuropneumoniae - Li, Huan; Liu, Feng; Peng, Wei; Yan, Kang; Zhao, Haixu; Liu, Ting; Cheng, Hui; Chang, Peixi; Yuan, Fangyan; Chen, Huanchun; Bei, Weicheng (Frontiers in Cellular and Infection Microbiology, 2018)
Gram-negative bacteria have evolved numerous two-component systems (TCSs) to cope with external environmental changes. The CpxA/CpxR TCS consisting of the kinase CpxA and the regulator CpxR, is known to be involved in the biofilm formation and virulence of Escherichia coli. However, the role of CpxA/CpxR remained unclear in Actinobacillus pleuropneumoniae, a bacterial pathogen that can cause porcine contagious pleuropneumonia. In this report, we show that CpxA/CpxR contributes to the biofilm formation ability of A. pleuropneumoniae. Furthermore, we demonstrate that CpxA/CpxR plays an important role in the expression of several biofilm-related genes in A. pleuropneumoniae, such as rpoE and pgaC. Furthermore, The results of electrophoretic mobility shift assays and DNase I footprinting analysis demonstrate that CpxR-P can regulate the expression of the pgaABCD operon through rpoE. In an experimental infection of mice, the animals infected with a cpxA/cpxR mutant exhibited delayed mortality and lower bacterial loads in the lung than those infected with the wildtype bacteria. In conclusion, these results indicate that the CpxA/CpxR TCS plays a contributing role in the biofilm formation and virulence of A. pleuropneumoniae.